Resilient remediation: addressing extreme weather and climate change, creating community value - Maco, Barbara; Bardos, Paul; Erickson‐Mulanax, Emerald; Hansen, Lara J.; Harclerode, Melissa; Hou, Deyi; Mielbrecht, Eric; Wainwright, Haruko M.; Yasutaka, Tetsuo; Wick, William D. (Wiley, 2018)
Recent devastating hurricanes demonstrated that extreme weather and climate change can jeopardize contaminated land remediation and harm public health and the environment. Since early 2016, the Sustainable Remediation Forum (SURF) has led research and organized knowledge exchanges to examine (1) the impacts of climate change and extreme weather events on hazardous waste sites, and (2) how we can mitigate these impacts and create value for communities. The SURF team found that climate change and extreme weather events can undermine the effectiveness of the approved site remediation, and can also affect contaminant toxicity, exposure, organism sensitivity, fate and transport, long‐term operations, management, and stewardship of remediation sites. Further, failure to consider social vulnerability to climate change could compromise remediation and adaptation strategies. SURF's recommendations for resilient remediation build on resources and drivers from state, national, and international sources, and marry the practices of sustainable remediation and climate change adaptation. They outline both general principles and site‐specific protocols and provide global examples of mitigation and adaptation strategies. Opportunities for synergy include vulnerability assessments that benefit and build on established hazardous waste management law, policy, and practices. SURF's recommendations can guide owners and project managers in developing a site resiliency strategy. Resilient remediation can help expedite cleanup and redevelopment, decrease public health risks, and create jobs, parks, wetlands, and resilient energy sources. Resilient remediation and redevelopment can also positively contribute to achieving international goals for sustainable land management, climate action, clean energy, and sustainable cities.
Keywords: climate change; extreme weather events; remediation resiliency; sustainable remediation; sustainable remediation forum